From welfare to work corporate initiatives and welfare reform - Perlmutter, Felice Davidson, 1931- (New York ; Oxford : Oxford University Press, 1997)
This work offers an analysis of how private corporations and industries can become effective partners with government in training and hiring welfare recipients for permanent positions. It provides a practical explanation of the specific steps needed to establish such a programme, with a case study.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public service employment -- United States; Welfare recipients -- Employment -- United States -- Case studies; Personnel management -- United States; Public welfare -- United States -- Case studies